2011
DOI: 10.1177/0021934711408901
|View full text |Cite
|
Sign up to set email alerts
|

Does Multicultural Education Improve Students’ Racial Attitudes? Implications for Closing the Achievement Gap

Abstract: The effects of multicultural education on the racial attitudes of students in prekindergarten through twelfth grade are examined in this meta-analysis. Multicultural education was operationalized for this study as programs and curricula dealing with racial and cultural diversity. The effect sizes of curricular intervention and reinforcement dimensions of multicultural education in suburban and urban settings among age groups 3-8 and 9-16 were compared to see the relative effectiveness of multicultural educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 27 publications
3
18
0
2
Order By: Relevance
“…That is, the variable is significantly and positively related to the attitude index, suggesting that respondents who took classes related to multiculturalism before entering their BSW program expressed more favorable attitudes. The finding is consistent with Okoye‐Johnson (), who found that pre‐college multicultural education in the US improved students' racial attitudes, particularly among the 9–16 age group. The finding also implies that pre‐college multicultural education, which has appeared in curriculum guidelines for elementary and high schools in Taiwan since the late 1990s, might have exerted its planned influence to improve ethnical attitudes (Lin et al., ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…That is, the variable is significantly and positively related to the attitude index, suggesting that respondents who took classes related to multiculturalism before entering their BSW program expressed more favorable attitudes. The finding is consistent with Okoye‐Johnson (), who found that pre‐college multicultural education in the US improved students' racial attitudes, particularly among the 9–16 age group. The finding also implies that pre‐college multicultural education, which has appeared in curriculum guidelines for elementary and high schools in Taiwan since the late 1990s, might have exerted its planned influence to improve ethnical attitudes (Lin et al., ).…”
Section: Resultssupporting
confidence: 89%
“…In contrast to these two studies, Okoye‐Johnson () conducted a meta‐analysis of whether multicultural education affects the racial attitudes of students in pre‐kindergarten through twelfth grade in the US. Her study reveals that multicultural education clearly improves students' racial attitudes.…”
Section: Correlates Of Ethnic and Racial Diversity Attitudes In The Lmentioning
confidence: 99%
“…Schooling initiatives that include Indigenous knowledge, perspectives, and cultures are seen to have a positive impact on Indigenous students' educational experiences, Indigenous family and school relationships, and the creation of welcoming and meaningful schooling environments for Indigenous families (Kanu, 2002(Kanu, , 2006(Kanu, , 2007Klump & McNeir, 2005;Kostenko & Merrotsy, 2009;Kovach, Carriere, Montgomery, Barrett, & Gilles, 2015;McKinley, Brayboy, & Castagno, 2009;Milne 2015Milne , 2016Whitley, 2014). For non-Indigenous students, Indigenous infused curriculum and schooling initiatives are seen as a mechanism to generate awareness of Indigenous cultures and perspectives, acceptance of cultural diversity, and to fight racism and prejudice (Direction Evidence and Policy Research Group, 2016;Okoye-Johnson, 2011;Segawa, 1994;UNESCO, 2003). Improved relationships between Indigenous Peoples and non-Indigenous Canadians may be a further benefit of non-Indigenous students learning about Indigenous Peoples.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, multicultural education, if adopted effectively, will help in reducing racial attitudes among students and improving diverse students learning to achieve academic success so they can be active participants in the society (Okoye-Johnson, 2011). Finally, providing challenging activities to all students, for example, encouraging multicultural music in arts education, can promote their cognitive thinking skills and creativity (Reed, 2010).…”
Section: Advantages Of Implementing a Multicultural Educational Systemmentioning
confidence: 99%